Characteristics of TPT initiation and completion among people living with HIV - L. Gunde; A. Wang; D. Payne; S. O'Connor; A. Kabaghe; N. Kalata; A. Maida; D. Kayira; V. Buie; L. Tauzi; A. Sankhani; A. Thawani; et al. (IJTLD Open)
BACKGROUND: TB preventive treatment (TPT) reduces morbidity and mortality among people living with HIV (PLHIV). Despite the successful scale-up of TPT in Malawi, monitoring and evaluation have been suboptimal. We utilized the Malawi Population-Based HIV Impact Assessment (MPHIA) 2020–2021 survey data to estimate TPT uptake and completion among self-reported HIV-positive persons. METHODS: We estimated the proportion of HIV-positive respondents who had ever undergone TPT, and determined the percentage of those currently on TPT who had completed more than 6 months of treatment. Bivariate and multivariable logistic regression were performed to calculate the odds ratios for factors associated with ever-taking TPT. All variables were self-reported, and the analysis was weighted and accounted for in the survey design. RESULTS: Of the HIV+ respondents, 38.8% (95% CI 36.4–41.3) had ever taken TPT. The adjusted odds of ever taking TPT were 8.0 and 5.2 times as high in the Central and Southern regions, respectively, compared to the Northern region; 1.9 times higher among those in the highest wealth quintile, and 2.1 times higher for those on antiretroviral therapy >10 years. Of those currently taking TPT, 56.2% completed >6 months of TPT. CONCLUSIONS: These results suggest low TPT uptake and >6 months’ completion rates among self-reported HIV+ persons. Initiatives to create demand and strengthen adherence would improve TPT uptake.